2004
DOI: 10.1023/b:lahu.0000015003.72223.63
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prior workplace behavior on subsequent sexual harassment judgments.

Abstract: A dual processing model of sexual harassment judgments predicted that the behavior of a complainant in a prior case would influence evaluations in an unrelated subsequent case. In the first of two experimental scenarios depicting social-sexual conduct at work, the female complainant's conduct was manipulated to be aggressive, submissive, ambiguous, or neutral. Half of the participants were asked to reflect upon the first scenario after reading it and before answering responsibility questions. The other half si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 49 publications
8
60
2
Order By: Relevance
“…The finding that women perceived all types of harassment as more serious than men runs counter to previous research which found that women tend to view more ambiguous, "hostile environment" types of harassment as more problematic than men, but that gender differences in perceptions disappear for clear cut cases of harassment, such as SC (e.g., Blumenthal 1998;O'Connor 1998;Rotundo et al 2001;Wiener et al 2004). However, it should be noted that other researchers have also found that women view SC as more problematic than men (O'Connor et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding that women perceived all types of harassment as more serious than men runs counter to previous research which found that women tend to view more ambiguous, "hostile environment" types of harassment as more problematic than men, but that gender differences in perceptions disappear for clear cut cases of harassment, such as SC (e.g., Blumenthal 1998;O'Connor 1998;Rotundo et al 2001;Wiener et al 2004). However, it should be noted that other researchers have also found that women view SC as more problematic than men (O'Connor et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…This hypothesis was based on other studies which indicate that gender differences in harassment perceptions are significant for less extreme, more ambiguous "hostile environment" harassment, but are not significant for unambiguous, extreme forms of harassment (e.g., SC; e.g., Blumenthal 1998;O'Connor 1998;Rotundo et al 2001;Wiener et al 2004).…”
Section: The Present Studymentioning
confidence: 99%
“…Three major areas of workplace sexual harassment literature concern the prevalence of sexual harassment, the effects of sexual harassment in the workplace, and how people make sexual harassment judgments (Wiener et al 2004). In the current study, we sought to integrate two of these areas of research (i.e., prevalence and judgments of what constitutes harassment) by examining how the prevalence of sexual harassment in different occupation types influences workers' perceptions of sexual harassment.…”
Section: Sexual Harassment Judgments Among Workers In Traditional Andmentioning
confidence: 99%
“…In the current study, we sought to integrate two of these areas of research (i.e., prevalence and judgments of what constitutes harassment) by examining how the prevalence of sexual harassment in different occupation types influences workers' perceptions of sexual harassment. Our hypothesis arose from the expectation that workers become more or less sensitive to the plight of sexual harassment complainants depending upon the frequency with which sexual harassment occurs, and the opportunities workers have to observe this misconduct, in their work environments (Wiener et al 2004(Wiener et al , 2005. We hypothesized that the direction of the impact of prior experience observing harassment at work depends upon the gender balance in the work place.…”
Section: Sexual Harassment Judgments Among Workers In Traditional Andmentioning
confidence: 99%
See 1 more Smart Citation